Intergenerational Transmission of Depressive Symptoms in Chinese Families: The Role of Mothers versus Fathers and Adolescent Perceptual Sensitivity - Sun K; Zhang X; Li P; Cao C (Psychology Research and Behavior Management, 2025)
Kexin Sun,1,* Xinting Zhang,2,* Ping Li,1 Cong Cao1 1School of Nursing and Rehabilitation, Shandong University, Jinan, People’s Republic of China; 2Department of Pediatrics, Qilu Hospital of Shandong University, Jinan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Cong Cao, School of Nursing and Rehabilitation, Shandong University, No. 44 West Wenhua Road, Jinan, Shandong Province, 250012, People’s Republic of China, Tel +86-88382268, Email caocong@sdu.edu.cnPurpose: Depression is well-known to be transmitted across generations, whereas the focus has often been on mother-child dyads. Little is known about the role of fathers and some inherited temperaments of adolescents, especially in Chinese families. This study is the first to explore the moderated mediation transmission mechanism of depressive symptoms, in which (i) the role of fathers was compared to that of mothers, and (ii) how adolescent perceptual sensitivity worked was particularly elucidated.Participants and Methods: A total of 738 Chinese adolescents (Mage = 12.80 ± 1.58 years; 47.2% girls) who were companied with one of their primary caregivers (mothers or fathers) were recruited, constituting two subsamples of mother-child (N = 508) versus father-child dyads (N = 230), respectively. Path models and the regions of significance approach were used to analyze the moderated mediation mechanisms.Results: Mothers and fathers both transmitted depressive symptoms to adolescents via their rejection parenting (indirect effect = 0.14, SE = 0.02, p < 0.001). However, adolescent perceptual sensitivity moderated the second half path of this mediation pathway among mother-child dyads (b = 0.09, SE = 0.04, p = 0.011), but not among father-child dyads (b = − 0.05, SE = 0.06, p = 0.348), and worked in a manner of diathesis-stress. Adolescent sex did not moderate this transmission mechanism (χ2 = 6.52, df = 3, p = 0.089).Conclusion: These findings suggest similarities and differences in the roles of mothers and fathers in the transmission risk of depressive symptoms in contemporary Chinese families, and highlight a diathesis-stress like moderation effect of adolescent perceptual sensitivity.Keywords: intergenerational transmission, depressive symptoms, caregiver rejection, perceptual sensitivity, mothers versus fathers